Politics and the practice of planning: The case of Zimbabwean cities. (March 2017) - Muchadenyika, Davison; Williams, John J.
Abstract: Planning is intrinsically a political process. This paper explores how the practice and profession of planning has been affected by politics. Available evidence in Zimbabwe shows that planning is problematized by unsettled national and local politics. However, contested politics can distort the intentions of a sound planning system through advancing political interests of politicians, the ruling elite. Interviews with political actors and planners allow an understanding of how politics has virtually eroded, if not eliminated, a sound planning system. This paper illustrates three dimensions of the relationship between politics and planning. First, the political contestation between the ruling and opposition party has severely undermined planning and its contribution towards coordinated development in cities. Second, planners often succumb to the politics of patronage at the expense of urban residents and town planning principles. Third, the integrity and credibility of planning is seemingly under constant threat from political actors. Highlights: Politics affects planning practice. Politics destabilises planning systems. The profession of planning requires regulation.